A Hymnal's Theological Significance - Westermeyer, Paul (Dialog, 2009)
A hymnal is a synthetic theological manual, which is a cue card to the church's sounding form. It lives in a stream with a soundscape, expresses a theological orientation, and stands as an ethical check and balance with a prophetic voice against the empire's addictions and entrapments.